Problems of FSES 3+ implementation at different stages of professional training of future tourism industry workers in the context of competence approach in education - Elena Alexandrovna Yeremina; Tatyana Nicolaevna Poddubnaya; Vladimir Gavrilovich Minchenko (Вестник Майкопского государственного технологического университета, 2023)
Integration of Russia into a single European educational space has determined the shift of the traditional education paradigm from a humanistic to a competence-based one, the quintessence of which is the formation of a competence system for students based on global trends in the achievement of education quality. The main feature of graduate vocational training programs implementation in the context of the European educational standard is the responsibility of educational organizations for the quality of the educational process, focused on the competence paradigm of modern education. This circumstance has formulated the research problem: what are the problems of FSES 3+ implementation at different levels of professional training of future workers in tourism industry in the context of a competence-based approach in education? The purpose of the research is to substantiate proposals for improving the process of training future tourism industry employees in the system of continuing professional education as a condition for an effective transition to FSES 3++. During the study, the following methods were used: analysis, synthesis, method of analogy. The results obtained: analysis of the FSES 3+ implementation according to the levels of professional training of college-baccalaureate-magistrature; problematic aspects of the implementation of federal educational standards of the third generation at different levels of professional training of future employees of the tourism industry (college- baccalaureate- magistrature) have been identified, measures to improve the process of professional training of students in the system of continuing professional education in the context of the transition to FSES 3++ have been proposed. Key conclusions: the identified problem aspects can guide the development of educational programs in accordance with FSES 3++ in the system of continuing professional education.